This I Believe - Dowd, Thomas B. (Tufts Archival Research Center, 2006)
Thomas Dowd proudly describes the difficulties endured by his mother and the enduring spirit, faith and dignity she displayed throughout her life as well as his determination to emulate the character of his mother.